Is Intent to Migrate Irregularly Responsive to Recent German Asylum Policy Adjustments? - Bernd Beber; Cara Ebert; Maximiliane Sievert (Institute of Labor Economics (IZA), 2024)
We investigate the extent to which asylum policies that aim to deter individuals from migrating irregularly in fact do so. We specifically consider effects of Germany's recent and high-profile asylum policy adjustments, which include accelerated asylum decision processes, the prospect of asylum processing outside of Europe, the introduction of a payment card to replace cash benefits, and an extended waiting period for native-level benefits. In order to estimate effects of these policy measures on irregular migration intent, we implement a conjoint experiment with 989 men aged 18–40 in four cities in Senegal, a population of most-likely migrants in a country where irregular migration to Europe is highly salient. We find that offshoring the asylum process significantly and substantially lowers irregular migration intentions across nearly all types of subjects. Extending the waiting time for native-level benefits only has a small, marginally significant effect on intent, and no effect among the poorest subjects and those that are most motivated to migrate internationally. Neither reducing asylum processing times nor replacing cash benefits with a payment card significantly alters intentions. We note that the presence or absence of an effect does not resolve political and normative questions concerning these policies, which are beyond the scope of this particular study.
Keywords: F22; J61; K37; 330; asylum policy; irregular migration; conjoint experiment